Participatory and Community-Driven Development in Urban Areas - World Bank Group (World Bank, Washington, DC, 2016)
This paper aims to contribute to learning on community engagement and community driven development (CDD) in urban areas. Specifically, the review describes the World Bank’s use of participatory and CDD approaches in urban areas between 2003 and 2013; identifies the challenges of using participatory and CDD approaches in the urban context; assesses lessons from the application of CDD in urban areas through case studies; and makes recommendations for a way forward in terms of operational approaches and further research to improve the application of CDD in cities. In conducting the study, the team engaged colleagues from social and urban development, and other relevant sectors in order to leverage cross-sectoral collaboration. The paper aims to provide a useful starting point for dialogue and collaboration to contribute to sustainable and inclusive cities. The findings of the review are targeted to task team leaders and national and local government officials who are interested in initiating, expanding, or scaling up projects with a participatory approach in urban areas.